2019
DOI: 10.1001/jamanetworkopen.2019.13619
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Chemoradiotherapy Regimens and Survival Among Patients With Nasopharyngeal Carcinoma

Abstract: This systematic review and meta-analysis assesses whether concurrent chemoradiotherapy is associated with improvement in survival outcomes for patients with locoregionally advanced nasopharyngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 75 publications
(156 reference statements)
0
27
0
Order By: Relevance
“…To perform plantar tumor growth assays, green fluorescent protein (GFP) -labeled 5-8F cell suspensions were injected into the footpads of nude mice. When the tumor grew to about 100 mm 3 , the two groups were injected with the corresponding agent. The tumor volume was measured every 3-4 days and calculated using the following formula: V=ab 2 /2 (V, volume; a, longitudinal diameter; b, lateral diameter).…”
Section: Tumor Xenograft Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform plantar tumor growth assays, green fluorescent protein (GFP) -labeled 5-8F cell suspensions were injected into the footpads of nude mice. When the tumor grew to about 100 mm 3 , the two groups were injected with the corresponding agent. The tumor volume was measured every 3-4 days and calculated using the following formula: V=ab 2 /2 (V, volume; a, longitudinal diameter; b, lateral diameter).…”
Section: Tumor Xenograft Modelmentioning
confidence: 99%
“…2 NPC has a high possibility of distant metastasis, while more than 70% of patients develop regional lymph node metastasis at the time of diagnosis, almost 20% of patients develop distant metastasis, mainly to the lungs or liver. 3 It is universally accepted that NPC is highly sensitized to radiation therapy (RT), which is the main treatment for NPC. 4 The major pattern of treatment failure is distant metastasis even after combined chemo-radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Two more recent systematic reviews and meta-analyses, not including NPC-0501, have confirmed better outcomes (overall survival, progression-free survival, locoregional control, and distant metastasis-free survival) with induction chemotherapy over chemoradiation alone; in one of them, adjuvant chemotherapy showed a lack of benefit for all endpoints. 4,5 In NPC-0501, no benefit in terms of locoregional control was observed in any of the treatment arms, although patients allocated to induction chemotherapy received less concomitant cisplatin. This finding suggests that induction plays a role in spatial cooperation.…”
mentioning
confidence: 99%
“…14,15 Recent meta-analyses out of China also demonstrated that the addition of induction chemotherapy instead of adjuvant chemotherapy can produce survival benefits. 16,17 The updated MAC-NPC analysis also shows that induction chemotherapy with concurrent chemoradiation improves disease control probability and survival over chemoradiation alone. 12 Because adjuvant chemotherapy and now induction chemotherapy improve survival for NPC patients treated with concurrent chemoradiation, the question remains: Which approach is superior?…”
mentioning
confidence: 99%